An Investigation into Information Needs of Rural Entrepreneurial Youth in the Context of Rural Revitalization: Based on the Survey in Heilongjiang, Jilin and Liaoning Provinces - ZHANG Yu, HUO Mingkui (Nongye tushu qingbao xuebao, 2022)
[Purpose/Significance] For rural areas, which are in a relatively information disadvantage, information can directly affect the probability of success of entrepreneurs, and it is important to clarify the characteristics and status of rural entrepreneurial youth's information needs to promote rural youth entrepreneurship development and rural revitalization. [Methods/Process] In this paper, we found through interviews and questionnaire research that the intensity of information needs of rural entrepreneurial youth in the field of entrepreneurship is influenced by factors such as age, income level, and industry characteristics. [Conclusions/Results] There are still more people in the group of rural entrepreneurial youth who have a lower level of understanding of entrepreneurial information, a lower level of information need satisfaction, and a lower level of recognition of public information services. In order to better mobilize the entrepreneurial enthusiasm of rural entrepreneurial youth and improve their success rate, the government and social forces should be given full play to promote the relevance, applicability and modern means of rural information services to promote the development of rural youth entrepreneurship.